PENGARUH SIZE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE - Dewinda Amalia Syahputeri; Teguh Erawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
Taxes are the biggest income for the State. But on the other hand, the companyconsiders taxes to be a burden that can reduce corporate profits. Due to thesedifferences, companies take advantage of loopholes in the Act to carry out taxevasion. This study aims to determine and analyze the effect of size and CSRon tax avoidance. The nature of this research uses quantitative and the dataused is secondary data with the sampling technique using purposive sampling.This study uses manufacturing companies in the consumer goods sector listedon the IDX in 2016-2019 as samples. Based on this method, 18 companieswere obtained. The results of this study indicate that CSR has no effect on taxavoidance, while company size has a negative effect on tax avoidance.